Quantum Technology in the Financial Sector: Econometric Analyses and Risk Management to Mitigate the Quantum Winter - Fırat, Emrah Hanifi (My University, 2024)
In today's rapidly evolving financial landscape, methods as econometric modeling, predictive analysis, and risk analysis are becoming increasingly important. These methods offer critical tools for understanding and managing the potential of quantum technology in the financial sector. Quantum technology can achieve fast and precise results in data analysis, risk management, portfolio optimization, and market forecasting. However, to realize these possibilities, we need to overcome technical challenges as well as financial and strategic barriers. This paper discusses scientific awareness and proposed solutions to 'Quantum Winter' especially in the financial sector. Mitigating the risk of a 'Quantum Winter' is possible through steps such as building strategic partnerships, conducting risk analysis, developing specialized capabilities, securing government support, and establishing appropriate regulations. Econometric modeling, predictive analysis, and risk analysis are indispensable tools to understand the potential of quantum technology in the financial sector and to achieve sustainable success.
Keywords: Quantum Computing; Quantum Winter; Quantum Optimization; Quantum Finance; Quantum Portfolio Optimization; Financial Econometrics